Peran Abdi Dalem Dalam Melestarikan Nilai-Nilai Budaya Jawa Dalam Komunikasi Interpersonal Di Keraton Kasunanan Surakarta Hadiningrat - Anindia Yulias Putri, Hayu; Riyanto, Buddy; Sihabuddin, Sihabuddin (Solidaritas, 2024)
Abdi dalem is a person who devotes himself to the Keraton. There are two groups of AbdiDalem in the Keraton Kasunanan Surakarta Hadiningrat, namely Abdi Dalem anon-anonKeraton and Abdi Dalem Garap Keraton. The purpose of this research is to determineAbdi Dalem's efforts in preserving Javanese cultural values in interpersonalcommunication at the Keraton Kasunanan Surakarta Hadiningrat. This study usedqualitative research methods. This type of research is descriptive qualitative.Determining the informants in this research used purposive sampling and the informantsin this research were Abdi Dalem Keraton Kasunanan Surakarta Hadiningrat, culturalfigures and the community. The location of this research is at the Keraton KasunananSurakarta Hadiningrat. Data collection uses observation, interviews and documentation.Data validity uses triangulation techniques. Using Miles and Huberman's (2014)interactive data analysis model. The results of the research show that Abdi DalemKeraton Kasunanan Surakarta Hadiningrat is a cultural preserver who has a positiveinfluence on society. This influence can be accepted by society as an example inunderstanding culture. The role of Abdi Dalem is nguri-uri or preserving Javanesecultural values with sincerity regarding the culture of the Keraton Kasunanan SurakartaHadiningrat. From the results of the analysis it can be concluded that Abdi Dalemcontributed to disseminating and preserving Javanese cultural values in interpersonalcommunication.Keywords: Abdi Dalem Keraton, Interpersonal Communication, Javanese CulturalValues